Multidimensional spectral factorization through the reduction method of multidimensional polynomial factorization - Mastorakis, Nikos E. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the (unsolved) Spectral Factorization problem, in m dimensions, is considered. A pure mathematical solution is attempted through the m-D polynomial factorization method of the Reduction. The necessary and sufficient condition is proved. The proposed method, which is also automated via a suitable computer code, is illustrated by a two-dimensional example.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka